DAYA TARIK METIL EUGENOL TERHADAP POPULASI LALAT BUAH (Bactrocera sp.) PADA BERBAGAI KETINGGIAN DAN WARNA PERANGKAP PADA PERTANAMAN CABAI MERAH - Jusmanto, Jusmanto; Nasir, Burhanudin; Yunus, Muhammad (AGROTEKBIS, 2019)
Bactrocera sp. is one of the important pests on crops of chili. Losing of the results caused by this pest attack can reach 80%, and even can be 100% if the control is not done immediately. The purpose of this research is to know the influence combination factors of color and the height of the traps on the number of fruit flies trapped in red chili. This research used Randomized Block Design (RBD) with factorial pattern consisting of 2 factors that are first factor consisting of yellow trap (W2), orange (W1), and clear (W3) and second factor is height of trap, that are height above of 50 cm ( T1), height of 75 cm (T2), and height of 100 cm (T3) respectively applied by Methyl eugenol. The research results showed that (W2, T2) (yellow and height of 75 cm) more effective control of fruit flies on Chili, average of  fruit flies trapped at the height and color is as much as 1758, and of the results of the yield from a height and color also effective because the average yield reached 2.28 kg/week when compared with the results of other productions. The use of methyl eugenol is very effective with the high number and variety of fruit flies trapped by 9113 with four types of fruit flies.